2018
DOI: 10.1063/1.5007197
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inhomogeneous barrier distribution in a Pt/(100)β-Ga2O3 Schottky diode via its temperature-dependent electrical properties

Abstract: β-Ga2O3 is an ultra-wide bandgap semiconductor with applications in power electronic devices. Revealing the transport characteristics of β-Ga2O3 devices at various temperatures is important for improving device performance and reliability. In this study, we fabricated a Pt/β-Ga2O3 Schottky barrier diode with good performance characteristics, such as a low ON-resistance, high forward current, and a large rectification ratio. Its temperature-dependent current–voltage and capacitance–voltage characteristics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…The WF variation is mainly produced by various surface treatment mentioned in Section II. The consideration of the WF variation is essential to mimic the barrier height inhomogeneity widely reported in Ga2O3 SBDs [13][22] [23].…”
Section: Machine Learningmentioning
confidence: 99%
“…The WF variation is mainly produced by various surface treatment mentioned in Section II. The consideration of the WF variation is essential to mimic the barrier height inhomogeneity widely reported in Ga2O3 SBDs [13][22] [23].…”
Section: Machine Learningmentioning
confidence: 99%
“…The most important part in SBD is the Schottky junction, so in the early research works on Ga 2 O 3 SBD, there are a substantial numbers of ones focusing on the study on the Schottky junction, mainly including the contact between Ga 2 O 3 and different Schottky electrodes (Ni、Cu、Au、Pt、TiN) [5759], the electron transport mechanism of the Schottky junction, the issues of interface states, barrier inhomogeneity and image force existing in the Schottky contact, and the methods of how to acquire perfect ohmic contact in the cathode interface [60, 61]. …”
Section: Schottky Barrier Diode Based On β-Ga2o3mentioning
confidence: 99%
“…With the increase of temperature, R on and J @2V became better, demonstrating that the device could work well at high temperature. In their following work, they further deeply investigated the temperature dependence of ideality factor and Schottky barrier height and found that this kind of temperature characteristics can be explained by the Gaussian distribution of barrier height inhomogeneity [61]. In 2018, they further optimized crystal growth parameters and improved the Sn doping concentration ( N d  −  N a  = 2.3 × 10 14  cm −3 ).…”
Section: Schottky Barrier Diode Based On β-Ga2o3mentioning
confidence: 99%
“…The Schottky barrier diodes (SBDs) based on β-Ga 2 O 3 material are being conducted early-stage research by several authors. Few studies have dealt with the electrical behavior of β-Ga 2 O 3 SBDs using β-Ga 2 O 3 single crystal grown using the several growth methods with different crystal orientations [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In these works, the most of the authors investigated the electrical conduction in β-Ga 2 O 3 SBDs under forward bias conditions where the thermionic emission current dominates the forward total current.…”
Section: Introductionmentioning
confidence: 99%